The effects of vasectomy on testicular tissue of mice: Histological changes and DNA fragmentation study - Al-Ani, Imad Matloub Dally; Salman, Mohammad Oda; Al-Wasiti, Estabraq A.; Thamir, Khalid T.; Al-Salihi, Anam R. (2013)
Introduction: We aim to investigate the effect of vasectomy on the histology of the testis as well as to evaluate DNA fragmentation in testicular tissue of male mice. Methods: Bilateral vasectomy was performed on 20 mature male mice; 10 control mice underwent sham-operation. After 6 weeks, the testes were evaluated for histological changes and DNA fragmentation by single cell gel electrophoresis (comet assay). Results: Marked alterations were observed in the testes of vasectomized mice, including degeneration of spermatids, thickened basement membrane, dilatation of the seminiferous tubules, exfoliation of germ cells, reduction in the seminiferous cell population, vacuolated appearance of the epithelium in the tubules and marked interstitial fibrosis. Single cell gel electrophoresis showed a highly significant (P<0.0001)increase in DNA damage among vasectomized mice (46.02%) compared with control group (%27.17)after six weeks of operation. Conclusion: Vasectomy induced deterioration in the seminiferous tubules associated with increased testicular cell’s DNA fragmentation. KEYWORDS: Vasectomy, comet assay, DNA degeneration, vas deferens.